Room temperature Monte Carlo study of the mechanical properties of thermoplastic polymers (2004)
ABSTRACT: he effect of the tensile test rate upon the mechanical properties of semicrystalline high-density polyethylene (HDPE) is studied by the Monte Carlo method. A two-dimensional lattice model is used, which considers first and second neighbour’s interactions between CH2-CH2 groups. Metropolis dynamics is implemented as energy minimization tool. Results reveal the existence of two distinguishable regions in the stress-strain curves. One of them is characterized by an elastic and linear behaviour below 0.27% of deformation where the elastic modulus is practically insensitive to the number of Monte Carlo steps, whereas at higher deformation the system exhibits a non-linear behaviour ascribed to the viscoelastic character of the material endorsed by a clear dependence of the relaxation modulus as a function of the strain rate. The relaxation behaviour of HDPE obtained in our simulation shows an exponential decrease of the stress as time increases, which agrees with experimental data.